2016
DOI: 10.1242/jcs.176446
|View full text |Cite
|
Sign up to set email alerts
|

Identification of RNF168 as a PML nuclear body regulator

Abstract: Promyelocytic leukemia (PML) protein forms the basis of PML nuclear bodies (PML NBs), which control many important processes. We have screened an shRNA library targeting ubiquitin pathway proteins for effects on PML NBs, and identified RNF8 and RNF168 DNAdamage response proteins as negative regulators of PML NBs. Additional studies confirmed that depletion of either RNF8 or RNF168 increased the levels of PML NBs and proteins, whereas overexpression induced loss of PML NBs. RNF168 partially localized to PML NBs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 61 publications
3
17
0
Order By: Relevance
“…RNF168 could only be detected within the nucleus, with a speckled appearance (Supplementary Figure S1). This nuclear distribution is consistent with the recently reported association of RNF168 with PML-NB [ 35 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…RNF168 could only be detected within the nucleus, with a speckled appearance (Supplementary Figure S1). This nuclear distribution is consistent with the recently reported association of RNF168 with PML-NB [ 35 ].…”
Section: Resultssupporting
confidence: 93%
“…Although RNF168 is amplified in some cancers [ 32 , 34 ], the observations reported below are the first to demonstrate the involvement of this gene in the control of cell survival and proliferation. Most recently, RNF168 has been shown to regulate PML nuclear bodies (PML NBs) [ 35 ], suggesting a potential mechanism for the regulation of proliferation and apoptosis by RNF168 described below.…”
Section: Introductionmentioning
confidence: 99%
“…They are widely distributed in mammalian cells and play an important role in a variety of cellular processes, such as transcription regulation, senescence, apoptosis, DNA repair and antiviral response (Pearson et al, 2000;Zhong et al, 2000b;Bernardi and Pandolfi, 2007;Everett and Chelbi-Alix, 2007;Giorgi et al, 2010;di Masi et al, 2016). Hundreds of proteins have been found to be associated with PML-NBs, either transiently or permanently, which may mediate the diverse functions of PML-NBs (Negorev and Maul, 2001;Weidtkamp-Peters et al, 2008;Shire et al, 2016). Defects in PML-NBs are closely related to pathogenesis, notably tumorigenesis (Salomoni and Pandolfi, 2002;de Thé et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…At the current stage, we formally cannot rule out that the phenotype obtained by ZNF451-1 RNAi knock down is indirect as impairment in sumoylation can have consequences on many cellular levels. Moreover, several mechanism regulating PML stability either in SUMO dependent pathways as described for RNF4 (Lallemand-Breitenbach et al, 2008;Tatham et al, 2008), RNF111 (Erker et al, 2013) and RNF168 (Shire et al, 2016) or in SUMO independent pathways as it was found for UHRF1 (Guan et al, 2013), E6AP (LouriaHayon et al, 2009), KLHL20 (Yuan et al, 2011), SIAH1/2 (Pietschmann et al, 2012) and RNF8 (Shire et al, 2016) are described in literature.…”
Section: Discussionmentioning
confidence: 89%